E-portal for tuition service and management - Koh, Edwin Wei Jian (Nanyang Technological University, 2021)
The increasing growth of Singapore household spending from S$650 million 15 years ago to S$1.4 billion on tuition since 2005. The average household spends around $88.40 per month. The high demand for the tuition industry is fuelled by the increase of average household income and the desire for their children to do better. As the low barrier entry of tutor, this resulted in a broad spectrum of quality of tutor. Hence, requiring the market for tutoring service is on the increasing trend, it would need an efficient way of handling the incoming demand. This paper is the report for the final year project entitled ‘E-Portal for tuition service and management’. This report aims to document the project’s progress and achievements up to date, the problems that may have encountered, and ongoing work. This report is 43 pages in length, excluding the cover page, abstract and reference.